SMEs’ export performance: the effect of learning orientation and innovativeness - Md Daud Ismail; Roshayati Abdul Hamid; Zizah Che Senik; Abdullah Sanusi Othman; Noor Hasni Juhdi (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the role of innovativeness and learning orientation on the internationalisation performance of small and medium entrepreneurial firms. Exporting has been the most appropriate mode of expansion into foreign market for SMEs due to lower risk and less resource commitment. The literature insists that future study should pay more attention on how SMEs improve export performance. Review of literature brings to the conclusion that innovativeness and learning orientation are pertinent in building the success of SMEs in export markets. Notwithstanding the existing investigation on the impact of innovativeness on performance, the results are inconclusive, reinforcing the need for investigation in the context of emerging market and SMEs. In addition, learning orientation composed of three dimensions namely managerial commitment, system perspective and openness and experimentation. Previous studies view learning orientation as summate of all three dimensions. Unlike previous studies, this study investigates the effect of each dimension on innovativeness. A conceptual framework was developed based on the resource-based view. Data were collected from small and medium business exporters in the manufacturing sector of an emerging market. A total of 220 respondents participated in this study. Data were analysed using structural equation modeling to test the hypotheses, and the results show that innovativeness is positively related to export performance. In addition, the findings reveal that managerial commitment is a function of innovativeness. System perspective, and openness and experimentation have no significant effect on innovativeness. Implications and limitations are also discussed in this study.